The AAA-ATPase Rea1 Drives Removal of Biogenesis Factors during Multiple Stages of 60S Ribosome Assembly - Baßler, Jochen (2010)
SUMMARY: The AAA(+)-ATPase Rea1 removes the ribosome biogenesis factor Rsa4 from pre-60S ribosomal subunits in the nucleoplasm to drive nuclear export of the subunit. To do this, Rea1 utilizes a MIDAS domain to bind a conserved motif in Rsa4. Here, we show that the Rea1 MIDAS domain binds another pre-60S factor, Ytm1, via a related motif. In vivo Rea1 contacts Ytm1 before it contacts Rsa4, and its interaction with Ytm1 coincides with the exit of early pre-60S particles from the nucleolus to the nucleoplasm. In vitro, Rea1’s ATPase activity triggers removal of the conserved nucleolar Ytm1-Erb1-Nop7 subcomplex from isolated early pre-60S particle. We suggest that the Rea1 AAA(+)-ATPase functions at successive maturation steps to remove ribosomal factors at critical transition points, first driving the exit of early pre-60S particles from the nucleolus and then driving late pre-60S particles from the nucleus.